SGIP1 modulates kinetics and interactions of the cannabinoid receptor 1 and G protein-coupled receptor kinase 3 signalosome - Gazdarica, Matej; Noda, Judith; Durydivka, Oleh; Novosadova, Vendula; Mackie, Ken; Pin, Jean-Philippe; Prezeau, Laurent; Blahos, Jaroslav (Journal of neurochemistry, 2022)
Cannabinoid receptor 1 (CB1R), a G protein-coupled receptor, plays a fundamental role in synaptic plasticity. Abnormal activity and deregulation of CB1R signaling result in a broad spectrum of pathological conditions. CB1R signaling is regulated by receptor desensitization including phosphorylation of residues within the intracellular C terminus by G protein-coupled receptor kinases (GRKs) that may lead to endocytosis. Furthermore, CB1R signaling is regulated by the protein Src homology 3-domain growth factor receptor-bound 2-like (SGIP1) that hinders receptor internalization, while enhancing CB1R association with β-arrestin. It has been postulated that phosphorylation of two clusters of serine/threonine residues, 425 SMGDS429 and 460 TMSVSTDTS468 , within the CB1R C-tail controls dynamics of the association between receptor and its interaction partners involved in desensitization. Several molecular determinants of these events are still not well understood. We hypothesized that the dynamics of these interactions are modulated by SGIP1. Using a panel of CB1Rs mutated in the aforementioned serine and threonine residues, together with an array of Bioluminescence energy transfer-based (BRET) sensors, we discovered that GRK3 forms complexes with Gβγ subunits of G proteins that largely independent of GRK3's interaction with CB1R. Furthermore, CB1R interacts only with activated GRK3. Interestingly, phosphorylation of two specific residues on CB1R triggers GRK3 dissociation from the desensitized receptor. SGIP1 increases the association of GRK3 with Gβγ subunits of G proteins, and with CB1R. Altogether, our data suggest that the CB1R signalosome complex is dynamically controlled by sequential phosphorylation of the receptor C-tail and is also modified by SGIP1.
Keywords: transportní proteiny; Kinetics; phosphorylation; cannabinoid receptor 1; threonin; β-arrestin; proteiny vázající GTP; serin; G protein-coupled receptors; GTP-Binding Proteins; G protein-coupled receptor kinase; receptory kanabinoidní; Carrier Proteins; Receptors, Cannabinoid; fosforylace; SGIP1; Serine; Threonine; kinetika; Phosphorylation